2012
DOI: 10.5430/ijba.v3n2p59
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Analysis of Factors Affecting Telecoms Customer Churn

Abstract: A major challenge facing telecoms business providers in Nigeria today is the continuous growing competition and customers' expectation of service quality and as such customers are able to choose among multiple service providers based on the level of satisfaction, affordability, and service quality of service providers. Customer demand and competition are forcing firms to cut loose from the traditional customer satisfaction paradigm, to adopt proactive strategies which will assist them to take the lead in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Han et al [14] discussed the relationship between consumer sentiment, switching barriers, customer satisfaction, and customer retention and believed that customer satisfaction was positively correlated with customer retention. After analyzing the reasons for customer churn, Oghojafor et al [15] put forward strategies for reducing churn rate. Stauss and Friege [16] believed that effective customer win-back should trace the reason for customer churn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Han et al [14] discussed the relationship between consumer sentiment, switching barriers, customer satisfaction, and customer retention and believed that customer satisfaction was positively correlated with customer retention. After analyzing the reasons for customer churn, Oghojafor et al [15] put forward strategies for reducing churn rate. Stauss and Friege [16] believed that effective customer win-back should trace the reason for customer churn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on customer defection has been largely on two issues. The first is to understand its triggering forces for which hypothesized influence of antecedents on customer churning is investigated through customer data available from service providers or through self-report surveys (Ahn et al , 2006; Eshghi et al , 2006; Hejazinia and Kazemi, 2014; Kim and Yoon, 2004; Kisioglu and Topcu, 2011; Oghojafor et al , 2012; Portela and Menezes, 2010; Wong, 2011). The second approach is to develop prediction models of customer behaviors (Coussement and De Bock, 2013; Coussement et al , 2010; Glady et al , 2009; Gorgoglione and Panniello, 2011; Gürsoy 2010; Hadden et al , 2005; Hou and Tang, 2010; Huang et al , 2010; Huang et al , 2012; Jahromi et al , 2014; Jamal and Bucklin, 2006; Lariviere and Van den Poel, 2004; Lin et al , 2011; Migueis et al , 2012; Neslin et al , 2006; Owczarczuk, 2010; Qi et al , 2009; Richter et al , 2010; Tsai and Chen, 2010; Tsai and Lu, 2009; Verbeke et al , 2011; 2014; Wang et al , 2009; Xia and Jin, 2008; Xiao et al , 2014; Xie et al , 2009; Yu et al , 2011; Zhang et al , 2012).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In previous studies, various antecedents of consumer defections have been studied in the context of different service industries. The antecedents include such clients’ demographic factors as residential areas, income levels and ages (Ahn et al , 2006; Kim and Yoon, 2004; Kisioglu and Topcu, 2011; Oghojafor et al , 2012; Portela and Menezes, 2010; Wong, 2011). It has been frequently shown that higher levels of perceived service quality and satisfaction lead to lower chances of consumer churn (Ahn et al , 2006; Eshghi et al , 2006; Hejazinia and Kazemi, 2014).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of discriminatory functions predicted the willingness of subscribers to drop their current service provider [2]. Discriminant analysis was employed to classify retail bank customers on the basis of users and non-users, and then they identified which variables contribute to the classification [3].…”
Section: Introductionmentioning
confidence: 99%